Literature review: synthesis of CuO (Copper Oxide) nanoparticles for thermal energy storage - Clarysa Satari; Rahmi Sabila Sidqi; Rian Febriyana Putra; Silmi Ridwan Putri; Asep Bayu Dani Nandiyanto (International Journal of Energetica)
This paper aims to provide a discussion of the methods used in the synthesis of CuO nanoparticles. A review of the CuO nanoparticle synthesis method was carried out from 65 articles from 2000 to 2021. The CuO nanoparticle synthesis methods described in this paper are electrochemical, sonochemical, sol-gel, biogenic, green synthesis, and hydrothermal methods. Each method used to synthesize CuO nanoparticles has advantages and disadvantages. Based on their advantages, electrochemical, sonochemical, green synthesis, and biogenic methods are environmentally friendly methods. Moreover, the hydrothermal and biogenic methods are simple methods with easy preparation. In its utilization, CuO nanoparticles can be used to divert heat energy. The addition of a volume of CuO nanoparticles into the nitrate salt can increase the thermal diffusivity and thermal conductivity used in solar power plants. Among the methods described, the hydrothermal method is the most effective and efficient technique. This is because the method is simple (without using any surfactant template), easy to vary the temperature, reactant concentration, and time variables on the growth of nanostructures. This paper is expected to provide some considerations regarding the synthesis method of CuO nanoparticles that can be used on an industrial scale based on the advantages of each method.